Recovery of human DNA from canine teeth exposed to direct heating of 300 °c at varying durations for forensic identification - Mahat N.A.; Dhevaseelan K.; Sharif N.A.; Khan H.O.; Azman A.R.; Layang E.; Ismail S.A. (American Institute of Physics Inc., 2024)
Dental remains one of the most reliable forensic means for identification, especially when facial recognition and fingerprints are inconclusive. Even though previous studies reported the possibility of retrieving DNA from teeth exposed to 300 °C, its recovery at varying exposure durations at that temperature remains unexplored. Therefore, in order to acquire forensic significance, in this research, unclaimed canine teeth obtained from clinics and hospitals were divided into 0 min exposure group together with 4 other groups, and were exposed to 300 °C at varying durations. The dental pulps were extracted and subjected to DNA analyses viz. DNA extraction, quantitation, amplification and visualization, as well as profiling. Although the concentrations of DNA were found to be negatively and moderately correlated (P < 0.05, r = -0.669, r2 = 0.447) to the durations of exposure, complete human DNA profiles for the 0 min exposed sample and sample exposed to 300 °C for 5 mins alone were successfully obtained. This finding deserves consideration for whenever human DNA evidence from teeth exposed to such temperature and duration of exposure needs to be considered for human identification in forensic practical caseworks.